La solvencia financiera mediante el modelo Grover y la prospectiva en empresas de transporte urbano en el cantón Riobamba - Mosquera Oleas, Josue Alexander (2024)
The paper titled "Financial Solvency through the Grover Model and Foresight in Urban Transport Companies in the Riobamba Canton" analyzes the financial situation of urban transport cooperatives in Riobamba, assessing their solvency using the Grover model and foresight analysis techniques. The research employs a quantitative approach with a non-experimental design and a correlational level, aiming to identify the relationship between financial solvency and future adaptability. Financial statements from seven transport cooperatives, collected from the Superintendency of Companies, were analyzed, along with surveys conducted with representatives of these companies. The results highlight that the companies face high levels of indebtedness and reliance on short-term financing, which jeopardizes their financial stability. The Grover model revealed significant insolvency risks in some cooperatives. Additionally, it was identified that implementing strategies based on financial foresight could improve the adaptability and sustainability of these companies. The conclusions emphasize the importance of strategic financial management, recommending the diversification of funding sources, reduction of debt, and the adoption of foresight tools to strengthen the sector's stability and competitiveness in the long term.